Experimental study on the thermal-hydraulic performance of a tube-in-tube helical coil air–fuel heat exchanger for an aero-engine. (15th March 2023) - Liu, Penghua; Wang, Renting; Liu, Shaobei; Bao, Zewei
Abstract: To fulfill the need for thermal protection in advanced aero-engines, a tube-in-tube helical coil (TTHC) air–fuel heat exchanger is recommended for a cooled cooling air system. This paper presents the testing of a TTHC heat exchanger. The results show that the heat exchanger effectively cooled the hot air because the compressed air temperature decreased from 823 K to 519 K with a flow rate of 0.0056 kg/s. The heat exchanger exhibited a maximum power–weight ratio of 26.6 kW/kg. The heat transfer rate was primarily determined by the air side heat transfer performance with a relatively high fuel flow rate. The density and viscosity of the fluid changed with the fluid temperature, resulting in a change in the pressure drop. Therefore, the pressure drops on the inner and annulus sides are related to the flow rate and heat transfer process. Large deviations were observed between the experimental data and calculated values by correlations reported in the literature, which were attributed to the differences in the experimental operating conditions and geometric parameters. A new empirical coefficient correlation for the annulus side was obtained using the Wilson plot method, which will be beneficial for researchers in designing similar air–fuel heat exchangers. Highlights: Cooling capability for TTHC air-fuel heat exchanger was experimentally investigated. The TTHC heat exchanger exhibits a maximum power–weight ratio of 26.6 kW/kg. Effects of various operating conditions on heat transfer and flow were analyzed. Pressure drops on inner and annulus sides are related to flow and heat transfer. A new heat transfer correlation for annulus side of heat exchanger was proposed.